Atmospheric pressure plasma as an activation step for improving protein adsorption on hydroxyapatite powder - Ozhukil Kollath, Vinayaraj [UNESP]; Put, Sofie; Mullens, Steven; Vanhulsel, Annick; Luyten, Jan; Traina, Karl; Cloots, Rudi (Wiley, 2015)
Protein adsorption on inorganic surfaces involves a complex mechanism which could be controlled by surface functionalization methods. A dry surface functionalization method for powders could be beneficial as compared to wet-chemical methods, since aspects like suspension preparation and subsequent drying can be avoided. This paper focuses on atmospheric pressure plasma technology for surface activation of hydroxyapatite powder as a carrier in oral administration applications, aiming at increasing the loading capacity of proteins. Hydroxyapatite powder is treated in N2 and N2-H2 atmospheric plasma processes within a static and a dynamic reactor. The influence of plasma activation on the protein adsorption isotherms, powder characteristics: particle morphology, specific surface area, and particle size distribution; have been discussed. The nature and amount of functional groups are studied by zeta potential measurements, thermogravimetric analysis, and titration analysis. Atmospheric plasma treatment increases the protein loading up to 37% when hydroxyapatite powder is treated in pure N2 plasma whereas that of powder activated using N2-H2 plasma increased by 13%. The increased protein loading can be attributed to the creation of nitrogen and oxygen containing moieties which cause an increased hydrophilicity after plasma treatment. Atmospheric pressure plasma as an activation step for improving protein adsorption on hydroxyapatite powder. Atmospheric pressure plasma treatment is evaluated as surface activation of hydroxyapatite powder, aiming at increasing the protein loading in carrier applications. HA powder is treated using atmospheric plasmas of N2 and a mixture of N2 and H2 within a static and a dynamic reactor. Protein loading increases more when HA powder is treated in N2 plasma.
Keywords: atmospheric pressure plasma; hydroxyapatite; powder; protein adsorption; surface modification